KEPENTINGAN AMERIKA SERIKAT MENARIK DIRI DARI JOINT COMPREHENSIVE PLAN OF ACTION (JCPOA) TAHUN 2018 - Purnama Dewi, Luh Gede Ria Riski Sari; Fasisaka, Idin; Suwecawangsa, Adi P. (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT This research aims to describe the interests of The United States of America withdrawing from the Joint Comprehensive Plan of Action (JCPOA) in 2018. This research uses qualitative descriptive method, and collected data from literary sources. The data in this research were analysed with two main concepts, which are rational choice and national security strategy. The results of this research found that the withdrawal of The United States from the JCPOA was due the nuclear development considered to threaten The United States national security and its interests in the Middle East. Efforts to attain the interest in the Middle East can be disrupted if Iran with its nuclear emerges as a new hegemon in the region, and emerges of threats to Israel’s security which is allies of the United States. Keywords: Joint Comprehensive Plan of Action, National Security Strategy, Rational Choice